Feasibility, efficacy, and safety of percutaneous MR‐guided ablation of small (≤12 mm) hepatic malignancies. Issue 2 (17th September 2018) - Weiss, Jakob; Hoffmann, Rüdiger; Rempp, Hansjoerg; Keβler, David‐Emanuel; Pereira, Philippe L.; Nikolaou, Konstantin; Clasen, Stephan
Abstract : Background: Percutaneous tumor ablation is commonly performed using computed tomography (CT) or ultrasound (US) guidance, although reliable visualization of the target tumor may be challenging. MRI guidance provides more reliable visualization of target tumors and allows for real‐time imaging and multiplanar capabilities, making it the modality of choice, in particular if lesions are small. Purpose: To investigate the feasibility, technical success, and safety of percutaneous MR‐guided ablation (RFA n = 27 / MWA n = 16) of small (≤12 mm) hepatic malignancies. Study Type: Retrospective case study. Population: In all, 45 patients (age: 61.1 ± 11.8) with hepatic malignancies and a lesion diameter of ≤12 mm scheduled for percutaneous MR‐guided tumor ablation based on a tumor board decision were included. Field Strength: A 1.5T MR system was used for planning, targeting, and monitoring. Assessment: Feasibility assessment included the detection of the target tumor, tumor delineation during MR‐fluoroscopy guided targeting, and the number of attempts needed for precise applicator placement. Technical success was defined as successful performance of the procedure including a safety margin of 5 mm. Safety evaluation was based on procedure‐related complications. Statistical Test: Frequency. Results: Tumor ablation (mean diameter 9.0 ± 2.1 mm) was successfully completed in 43/45 patients. Planning imaging was conducted without a contrast agent in 79% ( n = 37). In 64% ( n = 30), the target tumors were visible with MR‐fluoroscopy. In six patients (13%), planning imaging revealed new, unexpected small lesions, which were either treated in the same session ( n = 4) or changed therapy management ( n = 2) due to diffuse tumor progress. Postprocedural imaging revealed a technical success of 100% (43/43), with no major complications. During follow‐up, no local tumor progression was observed (mean follow‐up 24.7 ± 14.0 months) although 28% (12) patients developed new hepatic lesions distant to the ablation zone. No major complications were observed. Data Conclusion: MR‐guided ablation is a feasible approach for an effective and safe treatment of small hepatic malignancies. Level of Evidence : 4 Technical Efficacy : Stage 4 J. Magn. Reson. Imaging 2019;49:374–381.